Efficiency and productivity analysis of vegetable farming within root and tuber-based systems in the humid tropics of Cameroon - Ajapnwa Akamin; Jean-Claude Bidogeza; Jules René Minkoua N; Victor Afari-Sefa (Journal of Integrative Agriculture, 2017)
Abstract: The study analyzes the technical efficiency of vegetable farmers in root and tuber-based farming systems within selected sites of the humid tropics of Cameroon. Multistage sampling was used to collect primary data from a cross-section of vegetable farmers drawn from eight selected sites in Santa sub division, Northwest region of Cameroon. Stochastic frontier analysis was used to estimate the technical efficiency of vegetable farmer and to examine its determinants. The results showed that farmyard manure was the most productive factor input, followed by farm equipment and labor. The mean technical efficiency level was 67%, revealing production shortfalls and indicating possibilities of significantly increasing production with the current input levels. Female, as well as more educated farmers were found to be significantly more efficient than their counterparts. The results also showed that farmers become less technical efficient as farm sizes become larger. Our study findings suggest that smallholder farmers' access to manure, farm implements, and increased women participation in vegetable farming, will produce huge payoffs in vegetable production efficiency in Cameroon.